Pengaruh Model Concept Attainment terhadap Pemahaman Konsep Siswa pada Materi Klasifikasi Makhluk Hidup - Munisah, Munisah (Biocaster : Jurnal Kajian Biologi, 2023)
This study aims to determine the effect of using the concept attainment model on students’ conceptual understanding of the material on the classification of living things. Concept attainment is a learning model that allows students to learn to think critically, gain knowledge, and solve problems using real problems. The use of this concept attainment model is intended to improve students’ conceptual understanding of the material on the classification of living things. This study is a quantitative study with a quasi-experimental model using a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class using the concept attainment model and the control class using conventional learning methods. The instrument used in this study was a test, in the form of multiple choice questions to measure students’ cognitive learning outcomes. Data processing was carried out with the help of the SPSS program, namely the normality test, homogeneity test, and sample t-test. The results of the hypothesis obtained on students’ cognitive learning outcomes obtained a sig. 2-tailed value of 0.003, this value is smaller than the significance level of 0.05. Based on these data, it can be concluded that Ha is accepted and H0 is rejected, which means that there is an effect of using the concept attainment model on students’ conceptual understanding of the material on the classification of living things.